Photocatalytic reduction and scavenging of Hg(ii) over templated-dewetted Au on TiO2 nanotubes - Spanu, Davide; Bestetti, Alessandro; Hildebrand, Helga; Schmuki, Patrik; Altomare, Marco; Recchia, Sandro (Photochemical & Photobiological Sciences, 2019)
Gold-decorated TiO 2 nanotubes were used for the photocatalytic abatement of Hg(ii) in aqueous solutions. The presence of dewetted Au nanoparticles induces a strong enhancement of photocatalytic reduction and scavenging performances, with respect to naked TiO 2 . In the presence of chlorides, a massive formation of Hg 2 Cl 2 nanowires, produced from Au nanoparticles, was observed using highly Au loaded photocatalysts to treat a 10 ppm Hg(ii) solution. EDS and XPS confirmed the nature of the photo-produced nanowires. In the absence of chlorides and/or at lower Hg(ii) starting concentrations, the scavenging of mercury proceeds through the formation of Hg-Au amalgams. Solar light driven Hg(ii) abatements up to 90% were observed after 24 h. ICP-MS analysis revealed that the removed Hg(ii) is accumulated on the photocatalyst surface. Regeneration of Hg-loaded exhaust photocatalysts was easily performed by anodic stripping of Hg(0) and Hg(i) to Hg(ii). After four catalytic-regeneration cycles, only a 10% decrease of activity was observed.
CRIS-Team Scopus Importer:2019-05-28